Dianetics the evolution of a science - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Bridge Publications, Inc., 2007)
Book Description: Dianetics: The Evolution of a Science, this is the story of how L. Ron Hubbard discovered the reactive mind and developed the procedures to get rid of it. Originally written for a national magazine-published to coincide with the release of Dianetics: The Modern Science of Mental Health-it started a wildfire movement virtually overnight upon that book's publication. Here then are both the fundamentals of Dianetics as well as the only account of L. Ron Hubbard's journey of discovery and how he applied a scientific methodology to the problems of the human mind.